Peranan dan Kontribusi Islam Indonesia pada Peradaban Global - Faris Maulana Akbar (JURNAL INDO-ISLAMIKA, 2020)
The existence of Indonesian Islam which has its own characteristics and distinctions needs to be studied more deeply. Regarding the problem of radicalism that is currently being faced by the world, Indonesian Islam emerged and made a breakthrough with its moderate teachings. Finally, Indonesian Islam, which has recently been known as Islam Nusantara, has received worldwide attention as a reflection of a peaceful, friendly and tolerant Islam. Indonesian Islam is expected to be the pioneer of world peace. This article attempts to describe what Indonesian Islam can provide and how it can contribute to global civilization.